Clomiphene Citrate and Intrauterine Insemination: Analysis of 1, 531 Cycles by Time Trying to Conceive [6B]. (May 2018) - Stewart, Joshua; Panchap, Latha; Spandorfer, Steven D.
Abstract : INTRODUCTION: Clomiphene citrate and intrauterine insemination (CC/IUI) is often a first-line treatment for infertile couples. While it is well established that fecundity rates decrease with age, outcomes of CC/IUI cycles have not been well stratified by time trying to conceive (TTC). METHODS: All CC/IUI cycles performed under a single physician from January 1, 2010 to December 31, 2016 were included, totaling 1, 531 cycles in 536 unique couples. The following data were collected from an electronic medical record: age, obstetrical history, semen parameters, time TTC at cycle start, and cycle outcome. Stata IC 15 was used to calculate pregnancy rates. Chi-squared test was used to calculate p-values. RESULTS: The positive pregnancy rate (PPR) for couples TTC <1 year was 16.5%; 14.7% when TTC for 1-2 years, 15.4% when TTC for 2-3 years, and 8.6% when TTC for >3 years (p<0.05). The corresponding ongoing pregnancy rates (OPR) were as follows: 11.2%, 9.8%, 7.5%, 3.7% (p<0.05). In women <35 years old at cycle start, the corresponding OPRs were as follows: 13.1%, 11.3%, 8.6%, 4.3% (p<0.05); for women >35 years old at cycle start: 7.4%, 6.1%, 5.9%, 1.7% (p<0.05). CONCLUSION: Patients TTC with CC/IUI for <1 year have a higher PPR and OPR as compared to patients TTC for >1 year. Ongoing pregnancy rates further decline with each additional year TTC, and by 3 years of TTC, success rates dramatically decrease at all ages. This data provides important information to the clinician counseling infertile patients regarding when referral to a specialist and more aggressive treatments may be warranted.